Peran Stakeholder Dalam Membangun Citra Destinasi Wisata Di Dataran Tinggi Dieng Kabupaten Banjarnegara, Jawa Tengah - Hany Sintya Nida; I Nyoman Sunarta (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2021)
Recently, the government is echoing City Branding as one of the efforts in regional tourism development. One area in Central Java has a region that has well-known tourist attraction and has been established in the Development Master Plan Central Java Tourism as one of the mainstay tourist areas is Dieng Plateau Area (DPA). The DPA is managed by Wonosobo and Banjarnegara Regency. However, so far most tourists from outside the region consider the DPA only in the Wonosobo Regency area. This is certainly a loss for Banjarnegara Regency, in providing